2020
DOI: 10.3390/app10228120
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Study of Pump Units with Various Direct-On-Line Electric Motors Considering Cable and Transformer Losses

Abstract: The high energy intensity of the modern industry determines the high urgency of increasing the energy efficiency of production processes. However, a big number of motor types of enhanced efficiency classes are available on the market. The motor users can be confused about the choice of the right motor solution for a certain application. In this paper, to help with this choice the energy efficiency indicators of various types of electric motors in a low-power pump unit with a constant rotation speed are studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
0
5
0
1
Order By: Relevance
“…Rangkaian pengasutan pada motor induksi biasa menggunakan rangkaian pengasutan Direct On Line (DOL) yang merupakan rangkain pengasutan sederhana untuk menggerakan motor listrik secara konvensional. Metode rangkaian DOL ini paling mudah diterapkan, dan juga memiliki keuntungan mengemat energi dengan faktor daya tinggi kemudian mengurangi dalam konsumsi kabel dan trafo [10].…”
Section: Pendahuluanunclassified
“…Rangkaian pengasutan pada motor induksi biasa menggunakan rangkaian pengasutan Direct On Line (DOL) yang merupakan rangkain pengasutan sederhana untuk menggerakan motor listrik secara konvensional. Metode rangkaian DOL ini paling mudah diterapkan, dan juga memiliki keuntungan mengemat energi dengan faktor daya tinggi kemudian mengurangi dalam konsumsi kabel dan trafo [10].…”
Section: Pendahuluanunclassified
“…Table 1 presents the description of the components in Figure 1 and the approximate typical efficiency of each one of them. -Labels and MEPS for these devices tend to be stabilized by the theoretical limits of the dominant technologies so that the following improvements will come through new technologies in the case of electric motors [14,19], replacing the traditional three-phase Induction Motors with Squirrel Cage Rotor (SCIMs), by Permanent Magnet Synchronous Motors (PMSM), and by Motors Synchronous Reluctance (SynRM), to achieve the highest levels of IE4 and the future IE5 [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Kazakbaev et al [20] compared SCIMs class IE2 and IE3 fed directly from the network with PMSM and SynRM class IE4, fed through an Electronic Speed Variator (VSD), evaluating the energy savings over the life cycle of the motor-pump set and the payback period when replacing an IE2 class SCIM motor with an IE4 class motor. Kazakbaev et al [18] concluded that the IE4 electric motor, in addition to saving more energy due to its higher efficiency class, with the higher power factor, losses in the cable and the transformer were also reduced, recording a payback time of less than one year.…”
Section: Introductionmentioning
confidence: 99%
“…Paper [12] also discusses a comparison of the energy consumption of IM, DOL PMSM and DOL SynRM in a pumping application. In this case, the influence of the motor power factor on the losses in the cable and transformer is taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…This article, in contrast to [11,12], evaluates the energy savings when using static capacitors for reactive power compensation of various types of motors (IM of energy efficiency classes IE2 and IE3, DOL PMSM, DOL SynRM) in a pumping application. The energy savings when using motors of 3.7 kW, 60 Hz, four poles of various types in a pumping station and their payback period are assessed.…”
Section: Introductionmentioning
confidence: 99%